2011
DOI: 10.1177/1073191111429389
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Anxiety Sensitivity Index–3 in Clinical Samples

Abstract: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG geförderten)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 52 publications
7
67
1
5
Order By: Relevance
“…The Cognitive Concerns dimension had the highest correlation with depression and trait anxiety measures, despite correlations with these constructs were moderate for all the ASI-3 dimensions. In addition, the authors assessed known-groups validity, and reported that patients with PD had higher levels on the Physical Concerns dimension compared to patients with other anxiety disorders or those with disorders other than anxiety [10]. However, in this study patients with a diagnosis of other anxiety disorders (eg, SPh, GAD) were undersampled, and this limitation prevented to test for differences on the ASI-3 dimension scores between those disorders.…”
Section: Specificity Of the Asi-3 Across Anxiety Disorders And Other mentioning
confidence: 99%
See 1 more Smart Citation
“…The Cognitive Concerns dimension had the highest correlation with depression and trait anxiety measures, despite correlations with these constructs were moderate for all the ASI-3 dimensions. In addition, the authors assessed known-groups validity, and reported that patients with PD had higher levels on the Physical Concerns dimension compared to patients with other anxiety disorders or those with disorders other than anxiety [10]. However, in this study patients with a diagnosis of other anxiety disorders (eg, SPh, GAD) were undersampled, and this limitation prevented to test for differences on the ASI-3 dimension scores between those disorders.…”
Section: Specificity Of the Asi-3 Across Anxiety Disorders And Other mentioning
confidence: 99%
“…In a large clinical sample [10], the Physical Concerns dimension showed the highest correlation (moderate) with scales of body vigilance compared to the other dimensions. The Social Concerns dimension showed the highest correlation with a measure of fear of negative evaluation, and the correlation was moderate also for the Cognitive Concerns dimension.…”
Section: Specificity Of the Asi-3 Across Anxiety Disorders And Other mentioning
confidence: 99%
“…The significant role of anxiety sensitivity in anxiety pathology becomes apparent by comparing anxiety sensitivity scores between persons with different clinical symptom or between patients with versus without symptom [57]. Wheaton, Deacon, McGrath, Berman, and Abramowitz [58] observed that physical, social, and cognitive concerns subscale scores of patients with any anxiety disorder had significantly higher scores than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Allan i saradnici (Allan, Capron, Raines, & Schmidt, 2014) sugerišu da faktori nižeg reda ostvaruju značajne relacije sa širokim spektrom poremećaja, dok najčešće replicirani nalazi upućuju na pozitivnu povezanost ZFF i paničnog poremećaja, ZKF i depresivne simptomatologije i ZSS i straha od socijalne evaluacije i socijalne anksioznosti (Kemper, Bähr, Rüddel, & Hock, 2012;Olthuis, Watt, & Stewart, 2014;Osman et al, 2010;Taylor et al, 2007).…”
Section: Struktura Senzitivnosti Na Anksioznostunclassified
“…Da je ovakva upotreba specifičnih skorova potencijalno opravdana, govore i nalazi prethodnih studija (npr. Kemper et al, 2012;Olthuis et al, 2014;Osman et al, 2010;Wheaton et al, 2012). Kako bi se ova pretpostavka dodatno ispitala, bilo bi korisno u nekom od narednih istraživanja povećati broj stavki unutar subdomena da bi se, kako verujemo, povećala relijabilnost S faktora.…”
Section: Diskusijaunclassified